Fun Cognitive Games: A Play Therapy Approach to Alleviate Anxiety in Preschool Children with Thalassemia - Mil, Silvie; Auliya, Nabilla; Nurillah, Desi (Universitas Pendidikan Ganesha, 2024)
Anxiety is one form of unpleasant emotional response that is often felt by children with thalassemia during the hospitalization process. This study aims to analyze the effect of play therapy using fun cognitive games on anxiety disorders in children with thalassemia. The study used a quantitative pre-experimental approach with a One Group Pretest-Posttest design in preschool children undergoing treatment at the Mother and Child Hospital (RSIA). The sample was selected using a purposive sampling technique and involved five preschool children. The instrument used was an adaptation of the HARS instrument that had been validated and tested internally and externally. Data were collected through questionnaires and analyzed using the SPSS program. Hypothesis testing was carried out using the Wilcoxon test. The results of the pretest and posttest showed a decrease in anxiety disorders from the criteria for very severe anxiety disorders to mild anxiety disorders after children received fun cognitive games play therapy. The Wilcoxon test produced an Asymp.Sig. (2-tailed) value of 0.042 <0.05, which indicated a significant effect of fun cognitive games play therapy on anxiety disorders in preschool children with thalassemia at RSIA. The conclusion of this study is that the innovation of fun cognitive games play therapy is effective in reducing anxiety levels in preschool-age children with thalassemia. The implication of this study is that it can be a recommended intervention to support children's emotional well-being during hospitalization.